Efeitos da insularização sobre a comunicação acústica em aves do reservatório da UHE de Balbina, Amazonas - Santana, Thiago Bicudo Krempel (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
Environmental change may impose significant shifts to natural communication systems. In birds, such changes may trigger variations in acoustic signals used for communication over long distances. In tropical forests there is a high proportion of species that are vocally active, which, among other strategies, avoid overlap of signals in the acoustic space by calling in narrow frequency bands. On the other hand, islands have fewer species and less saturated acoustic space, allowing for acoustic signals to vary in spectral and temporal properties. At the same time, these properties are adapted in a way that optimizes the propagation distance in the predominant habitat. Despite acoustic signals being relatively well studied in natural systems, it is unclear whether insularization promoted by human activity on natural landscapes in recent time is able to trigger changes in communication systems in suboscines birds. This study investigated the variability in spectral and temporal properties of acoustic signals of two suboscines birds (Lipaugus vociferans and Tyranneutes virescens) on islands of an artificial lake created by damming the Uatumã River in the state of Amazonas, Brazil. Specifically, I tested whether this variability was related to variation in the islands area and isolation, as proxies of the acoustic community, while considering the vegetation structure present on the islands. I obtained recordings from 67 L. vociferans individuals and 69 T. virescens on 12 islands across the lake, totaling 322 and 345 songs recordings for each species, respectively. Variations in bandwidth of L. vociferans songs were related to the area and isolation of the islands, whereas such relationships were not observed for songs of T. virescens. In both species, average lower and peak frequencies of songs were related to variation in vegetation structure, where higher frequencies were found in islands with greater basal area. The temporal properties of the songs of the two species were not associated with variations in area, isolation and structure of vegetation. Our results show that even in suboscines species, where the songs are innate, subtle changes in the environment in a short time, can lead to changes in spectral acoustic properties. Future studies should evaluate the potential evolutionary impacts that these changes in acoustic signals may have, by assessing genetic variation among birds inhabiting islands in this system.
Keywords: Adaptação acústica; Aves; Character release